Analysis of Transformational and Transactional Leadership in Enhancing Employee Motivation and Productivity - Novitasari, Aas; Kala, Veronika Natalia; Hapiyansyah, Mohammad (Lentera Ilmu Nusantara, 2025)
In the era of globalization and rapid technological advancement, modern organizations are required to continuously enhance their efficiency and effectiveness in order to face increasingly intense competition. In this context, leadership becomes a critical factor that determines an organization’s success in achieving its strategic goals. Effective leadership is not only capable of directing and managing resources, but also of shaping strategy, building a positive organizational culture, and creating a conducive work environment for improved individual and team performance. This study highlights the role of transformational and transactional leadership styles in enhancing employee performance, job satisfaction, and organizational commitment. Transformational leadership is seen as capable of inspiring and motivating employees to achieve higher performance through a clear vision, empowerment, and concern for individual needs. Conversely, transactional leadership emphasizes a reward and punishment system based on the achievement of predetermined targets. Furthermore, work environment and work motivation are considered as important variables that can strengthen or weaken the influence of leadership styles on performance. Although previous studies have discussed the direct impact of leadership on performance, there remains a gap in understanding the mediating or moderating roles of other factors such as motivation and work environment. Therefore, this study aims to provide a more comprehensive and in-depth understanding of the relationship between leadership styles, work motivation, work environment, and organizational performance in facing today’s managerial challenges.